2004
DOI: 10.1007/s00467-004-1498-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with antenatally detected pelviureteric junction obstruction

Abstract: We investigated the outcome of patients with antenatally detected pelviureteric junction (PUJ) obstruction treated either conservatively or surgically. The series comprised 68 such patients, 54 with unilateral obstruction. Of the unilateral cases, 22 units were treated conservatively, 21 underwent early and 11 late surgery. Of the bilateral cases, 18 units were treated conservatively, 9 underwent early pyeloplasty, whereas 1 underwent later surgery. Among the conservatively treated unilateral cases, none of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
0
19
0
7
Order By: Relevance
“…Cornford and Rickwood [20] also reported that pyeloplasty failed to significantly improve renal function in patients born with UPJO and impaired renal function. Ylinen et al [23] found that in the group with early surgery, the primarily normal function remained unchanged, but in kidneys with poor function, recovery may be minimal despite pyeloplasty. Research on animal models has also confirmed that removal of obstruction did not reverse renal injury, mainly because of the progression of fibrosis [24].…”
Section: Discussionmentioning
confidence: 96%
“…Cornford and Rickwood [20] also reported that pyeloplasty failed to significantly improve renal function in patients born with UPJO and impaired renal function. Ylinen et al [23] found that in the group with early surgery, the primarily normal function remained unchanged, but in kidneys with poor function, recovery may be minimal despite pyeloplasty. Research on animal models has also confirmed that removal of obstruction did not reverse renal injury, mainly because of the progression of fibrosis [24].…”
Section: Discussionmentioning
confidence: 96%
“…Most kidneys in each functional range improved when obstruction was relieved. Arelative renal flow > 51% in the obstructed kidney by 99m technetium mercaptoacetyl triglycine study was not always beneficialin prognosticating, and may be a warning of impending decompensation in a minority [18,19].…”
Section: Prognosismentioning
confidence: 90%
“…7 In terms of initially poor functioning kidney, congenital damage may influence recoverability of the affected kidney. In a recent study Ylinen et al 18 reported that no improvement occurred in the kidney with <30% preoperative DRF regardless of successful surgical correction. Although Ulman et al 5 described in some children renal function may take years to improve to > 40%, our data did not support their findings.…”
Section: Discussionmentioning
confidence: 99%